FORM AND FUNCTION OF THE THAK-THAKAN PROCESSION IN THE CLEANING RITUAL OF BELIKANGET TAMBAKBOYO TUBAN VILLAGE: BENTUK DAN FUNGSI PERTUNJUKAN ARAK-ARAKAN THAK-THAKAN DALAM RITUAL BERSIH DESA BELIKANGET TAMBAKBOYO TUBAN - Indrawasih, Surati; prasetyanti sekti, retnayu (Solah, 2025)
Thak-thakan art is a traditional performing art originating from Tuban Regency, precisely in Tambakboyo District, East Java. The show features a mythical animal figure that is considered a symbol of protection from threats and disturbances. In the tradition of cleaning the village in Belikanget Village, the community carries out the Thak-thakan Procession which involves all villagers to surround the village and is believed to be able to ward off dangers from all directions. This study aims to describe the form and function of the Thak-thakan procession in the village cleaning procession in Belikanget Village. The method used is qualitative descriptive with data collection techniques in the form of observation, interviews, and documentation, as well as data analysis techniques including reduction, presentation, and conclusion drawn. The validity of the data is guaranteed by triangulation of sources, techniques, and time. The results of the study show that the art of Thak-thakan is a cultural heritage that is still upheld by the people of Belikanget Village. In addition to functioning as a ritual means to ward off danger, the Thak-thakan procession also functions as entertainment, strengthening social solidarity, and cultural preservation. This procession is carried out by bringing tumpeng filled with produce as an expression of gratitude. The existence of this art reflects the strong traditional values and cultural identity of the people of Belikanget Village which have been inherited from generation to generation. Thus, the art of Thak-thakan can continue to be preserved as part of the valuable local cultural wealth. Keywords: Procession, Thak-thakan, function, and village cleanliness